Brain-derived blood biomarkers in multiple sclerosis—current trends and beyond - Anandan, Shamundeeswari; Maciak, Karina; Breinbauer, Regina; Mostafavi, Sepideh; Kvistad, Christopher Elnan; Torkildsen, Oivind; Myhr, Kjell-Morten (Frontiers in Immunology, 2025)
Multiple sclerosis (MS) is a chronic inflammatory and neurodegenerative disease of the nervous system and a main cause of neurological disability in young adults. Most disease-modifying therapies are administrated as long-term maintenance therapies and may, thereby, increase the risk of infections and other immune-mediated side effects. In the last years, several cerebrospinal fluid and soluble blood biomarkers have been suggested as potential key tools for diagnosis, prognosis, and treatment monitoring of MS. Recently, the specific ability of brain-derived blood extracellular vesicles (EVs) that cross the blood-brain barrier into the bloodstream, reflecting the current immune status of the central nervous system, has kindled interest as potential biomarkers. In this review, we discuss the current trends of clinical brain-derived blood biomarkers, with a special focus on the emerging role of brain-derived blood EVs in MS.